2008
DOI: 10.1103/physrevlett.100.105004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Control of Laser-Produced Proton Beams

Abstract: The emission characteristics of intense laser driven protons are controlled using ultrastrong (of the order of 10(9) V/m) electrostatic fields varying on a few ps time scale. The field structures are achieved by exploiting the high potential of the target (reaching multi-MV during the laser interaction). Suitably shaped targets result in a reduction in the proton beam divergence, and hence an increase in proton flux while preserving the high beam quality. The peak focusing power and its temporal variation are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 17 publications
3
58
0
Order By: Relevance
“…While some of the focussing techniques, such as laser-driven micro-lenses 6 , magnetic quadrupoles 7 , pulsed solenoids 8 , allow a degree of spectral tailoring in addition to the divergence control, they typically captures a small portion of the divergent proton beam. Other techniques such as ballistic focussing from curved targets 9 or self-driven quasi-electrostatic lenses 10 act on the full beam, but they either provide achromatic focussing or only partial reduction in divergence. Therefore innovative approaches are a) Electronic mail: s.kar@qub.ac.uk required to enable beam control and optimisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some of the focussing techniques, such as laser-driven micro-lenses 6 , magnetic quadrupoles 7 , pulsed solenoids 8 , allow a degree of spectral tailoring in addition to the divergence control, they typically captures a small portion of the divergent proton beam. Other techniques such as ballistic focussing from curved targets 9 or self-driven quasi-electrostatic lenses 10 act on the full beam, but they either provide achromatic focussing or only partial reduction in divergence. Therefore innovative approaches are a) Electronic mail: s.kar@qub.ac.uk required to enable beam control and optimisation.…”
Section: Introductionmentioning
confidence: 99%
“…The EM pulse effectively carries a neutralizing current which attempts to restore charge neutrality in the irradiated region of the target, following its positive charge-up due to the prompt escape of a fraction of hot electrons produced during the interaction [10][11][12] . The experimental data characterising the propagation of the pulse is presented, followed by data showing chromatic focussing of the TNSA proton beam.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the upcoming increase in repetition rate of these lasers (now a few shots per hour) will soon increase with the development of fiber [41] or diode-pumped lasers [42,43]. The smooth electric field profiles [19] and the simple structure (potentially a single target [44]) of the microlens make this technique compatible with quick, repeatable lasers making laser-based short-pulse neutron sources even more attractive.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…Kar et al [45] showed beam focusing by using rectangular or cylindrical hollow lens attached to a foil target. Offermann et al [46] found theoretically and experimentally that ion divergence depends on the thermal expansion of the co-moving hot electrons, resulting in a hyperbolic ion beam envelope.…”
Section: Beam Focusingmentioning
confidence: 99%